-27=r/12-18

Simple and best practice solution for -27=r/12-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -27=r/12-18 equation:


r in (-oo:+oo)

-27 = r/12-18 // - r/12-18

18-(r/12)-27 = 0

-1/12*r-9 = 0 // + 9

-1/12*r = 9 // : -1/12

r = 9/(-1/12)

r = -108

r = -108

See similar equations:

| -2(v+3)+3v= | | 65=12x+5 | | 5x^2-34x+68=0 | | -12+7(d-1)+14-d=p | | 4x+7=3(x+2)+(x+2)5 | | X+2=-x-10 | | 2(-7+9k)= | | 3m+3z=23 | | 5w-2(3x-5w)-5x= | | a=1.9044+1.23(3) | | 4x/-710 | | 7c+2c+8c-3= | | m-13=-8/2m | | j/6=1/3 | | 10x+30=20+5x | | 6x+9=89 | | 2k-11=1+4k | | 63xpi=x | | 8(3n-4)= | | 38n=15 | | -6(-3n+5)= | | 2/5x-3=3 | | 2x^2+20x+200=0 | | 1-3x=3x+19 | | 3x+3=-3x-9 | | -5k^2+10k=0 | | -9+6(4y-8)= | | H(x)=Ln(3x-4) | | 0.27m+2=0.35m | | 924=11y+143 | | 1-g+s-2g+3(g-2)=p | | 16t^2-80t-64=0 |

Equations solver categories